Justice and justification reflective equilibrium in theory and practice - Daniels, Norman 1942- (Cambridge studies in philosophy and public policy, 1996)
We all have beliefs, even strong convictions, about what is just and fair in our social arrangements. How should these beliefs and the theories of justice that incorporate them guide our thinking about practical matters of justice? This wide-ranging collection of essays by one of the foremost medical ethicists in the USA explores the claim that justification in ethics, whether of matters of theory or practice, involves achieving coherence between our moral and non-moral beliefs. Amongst the practical issues addressed in the volume are the design of health-care institutions, the distribution of goods between the old and the young, and fairness in hiring and firing. In combining ethical theory and practical ethics this volume will prove especially valuable to philosophers concerned with ethics and applied ethics, political theorists, bioethicists, and others involved in the study of public policy